KAJIAN (K3) PELEDAKAN DALAM PENGENDALIAN BAHAYA DAN RISIKO SISTEM PENAMBANGAN DI PT HANSINDO MINERAL PERSADA - Zikrina .; M. Khalid Syafrianto; Fitriana Meilasari (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2022)
PT. Hansindo Mineral Persada is a granite mining company located in Peniraman Village, Sungai Pinyuh District, Mempawah Regency, West Kalimantan. This company conducts mining by blasting. Occupational Safety and Health (K3) is an important thing and needs to be considered by the company to minimize and prevent potential hazards and risks in work activities. The method in this study uses the HIRARC (Hazard Identification Risk Assessment and Risk Control) method. The data analysis is divided into 3 stages, namely, hazard identification, risk assessment and risk control. The results obtained from this study are that there are 26 potential hazards and 28 risks from 4 drilling activities and 6 blasting activities. From the results of the analysis of the risk level, there are 3 levels of assessment with the result that the low risk level is small, namely 7% with 2 risks, the medium risk level is 57% with 16 risks and high the high risk level is 36% with 10 risks. Recommendations for risk control using the hierarchy of controls are obtained, Engineering is 10% with 2 risks, administration is 45% with 10 risks and Personal Protective Equipment (PPE) is 45% with 10 risks.